New Avenues of Research for Nanoparticle Drug Delivery Systems - Prado-Gotor, Rafael (MDPI - Multidisciplinary Digital Publishing Institute, 2023)
Knowledge of the different elements that determine the optimal method for drug loading and delivery nanosystems using nanoparticles of different natures is experiencing a remarkable boom in many scientific fields, especially in medicine, chemistry, biology, materials science and molecular biotechnology. Not only is it necessary to fully understand what type of nanoparticle is most appropriate in each particular situation, but the interactions of the used nanoparticle with the system under study and the analysis of the release process are important as well. To design nanoparticle drug delivery agents well, a high ratio of drug to nanoparticles must be achieved. Furthermore, biocompatibility and knowledge of the time that the release process takes are fundamental factors for the construction of operative NPs as drug delivery vectors. Today, efforts on the development of appropriate nanosystems are focused on producing new materials that release drugs in a sequential manner with different therapeutic efficacy. To achieve optimal results among researchers from various areas, this reprint of Nanomaterials will try to consider all of these key factors that need to be taken into account for nanosystems to be suitable for drug release. "New Avenues of Research for Nanoparticle Drug Delivery Systems" brings together the recent research articles published in Nanomaterials. Specifically, five original research articles, with one of them being a review, were published by authors from different countries on current issues in this field of research.